Birds of New Forest : New Additions - Mohan, Dhananjai (Indian Forester, 1993)
Briefly mentioning the geographical parameters and avifaunal richness of New Forest campus situated in Debradun Valley in Uttar Pradesh, the author has presented his observations on birds during last 8 years. The author has listed 45 species of birds which were sighted by him in addition to those sighted and listed earlier by Joseph George three decades ago.